CONSTRUCTION DE LA MEMOIRE COLLECTIVE DANS LES SUJETS DU BACCALAUREAT LETTRES ET PHILOSOPHIE - BENSOLTANE Sabrina (My University, 2023)
Summary The study explores the construction of collective memory through French texts in the baccalaureate exams for literature and philosophy since 2008, in response to the revocation of Article 4 of the 2005 law. The first chapter introduces this context, provides a literary review of genre definitions, and examines the relationship between individual memory, history, and collective memory, presenting a methodology for corpus analysis. The second chapter categorizes the corpus to examine historical and memorial aspects, covering the colonial context and the war of national liberation. The analysis addresses the ideological foundations of colonialism, war crimes, forms of resilience, resistance, and armed struggle, as well as sacrifices and traumas for freedom, shedding light on the educational strategy in the construction of Algerian collective memory ----------------- الملخص تستكشف الدراسة بناء الذاكرة الجماعية من خلال نصوص اللغة الفرنسية في امتحانات البكالوريا في الآداب والفلسفة منذ عام 2008، رداً على إلغاء المادة 4 من قانون عام 2005. يقدم الفصل الأول هذا السياق، ويقدم مراجعة أدبية لتعاريف النوع الأدبي ويستكشف العلاقة بين الذاكرة الفردية والتاريخ والذاكرة الجماعية، مقدماً منهجية لتحليل النصوص. يصنّف الفصل الثاني النصوص لفحص الجوانب التاريخية والذاكرية، والتي تشمل السياق الاستعماري وحرب التحرير الوطني. تتناول التحليل الأسس الإيديولوجية للاستعمار، وجرائم الحرب وأشكال الصمود والمقاومة والنضال المسلح، وكذلك التضحيات والصدمات من أجل الحرية، مسلطة الضوء على استراتيجية التعليم في بناء الذاكرة الجماعية الجزائرية. ---------------- Résumés L'étude explore la construction de la mémoire collective via des textes de français au baccalauréat en lettres et philosophie depuis 2008, en réaction à l'abrogation de l'article 4 de la loi de 2005. Le premier chapitre introduit ce contexte, offre une revue littéraire des définitions du genre et explore la relation entre mémoire individuelle, Histoire et mémoire collective, en présentant une méthodologie d'analyse du corpus. Le second chapitre catégorise le corpus pour examiner les aspects historiques et mémoriels, couvrant le contexte colonial et la guerre de libération nationale. L'analyse aborde les fondements idéologiques du colonialisme, les crimes de guerre et les formes de résilience, de résistance et de lutte armée, ainsi que les sacrifices et traumatismes pour la liberté, mettant en lumière la stratégie éducative dans la construction de la mémoire collective algérienne
Keywords: collective memory; colonialism; war; construction; ذاكرة جماعية، استعمار، حرب، بناء; mémoire collective; colonialisme; guerre construction